Pedagogical Content Validation of an Ethnomathematics-Based Role-Playing Game for Teaching Geometric Transformations - Lustanti Rara Halis; Yurizka Melia Sari (Journal of Mathematical Pedagogy (JoMP), 2026)
Students frequently experience difficulties in learning geometric transformations because the concepts are highly abstract and require well-developed spatial reasoning. Integrating ethnomathematics into interactive learning media offers a promising pedagogical approach to contextualize mathematical concepts while promoting students' spatial ability. This study aimed to develop and examine the content validity of an ethnomathematics-based educational role-playing game (RPG), namely Tapak Citra, which incorporates the cultural heritage of Gedog Tuban batik to support junior high school students' learning of geometric transformations. The study employed a development research approach focusing on expert validation. Two mathematics education experts and two educational media experts evaluated the game using validation instruments, and the level of agreement was analysed using Gregory's content validity formula. The findings revealed a material validity index of 1.00 and a media validity index of 0.72, indicating that the developed game possesses high content validity and is appropriate for classroom implementation. These findings suggest that ethnomathematics-based role-playing games have the potential to become meaningful pedagogical tools for supporting students' spatial ability through culturally contextualized mathematics learning. Nevertheless, the study was limited to expert validation without classroom implementation. Future studies should investigate the practicality and effectiveness of the game in improving students' spatial ability and learning outcomes in geometric transformations